A comparative study on mechanical and rheological properties of ternary rubber blends. Issue 1 (January 2021) - Abdelsalam, Amir A; Araby, Sherif; El-Sabbagh, Salwa H; Abdelmoneim, Ahmed; Hassan, Mohsen A
Polymer blends lead to producing a new class of plastics, which may have better properties than being individual. In this study, the ternary blends of natural rubber (NR)/styrene-butadiene rubber (SBR)/nitrile rubber (NBR) were prepared via melt compounding, and then the physicomechanical properties of ternary NR/SBR/NBR blends were investigated. NR content was kept constant at 30 phr, while SBR and NBR fractions were varied simultaneously. The effect of the addition of 3 phr of ultrablend 4000 as compatibilizer on the compatibility of the rubber blends was studied. The results revealed that the use of the compatibilizer has significantly resulted in the clear stability of the scorch time and the optimum cure time of the blends. Tensile strength; stress at 100%, 200%, and 300% elongations; elongation at break %; compression strength; and compression set increase with the NBR content. There was a dramatic rise in the value of swelling ratio with the decrease of NBR. Moreover, the dynamic mechanical analysis showed some shifts in glass transition temperatures for blends to higher and lower temperatures as a function of the composition, which indicates the partial miscibility between the contributing components. Scanning electron microscopy of the tear fracture surfaces indicated that incorporation of NBR in the blends resulted in better adhesion of ternary blends and improved the tensile properties of ternary blends.